Foundations of agricultural education - Talbert, B. Allen, 1961-; Croom, Barry; LaRose, Sarah E., 1985-; Vaughn, Rosco C., 1943-; Lee, Jasper S. (Purdue University Press, 2022)
"Foundations of Agricultural Education, Fourth Edition is designed for college students in agricultural education and others interested in agricultural education as fundamental preparation for the profession. Teachers of agricultural education and those in support roles will find this book to be a helpful resource. This fourth edition is updated to reflect current educational theory and practices, and includes changed laws and initiatives since the third edition. This updated textbook is appropriate for both introductory and advanced courses. Each chapter begins with a scenario designed to engage the learner in thinking about the content of that chapter and draws from relevant research and literature. Photos, illustrations, and tables provide greater context to key concepts, and every chapter concludes with questions for review and discussion, as well as additional activities designed to guide the learner into further exploration. Foundations of Agricultural Education, Fourth Edition is an engaging, immersive guide that will help prepare the next generation of agricultural educators"--